Exploring the job (dis)satisfaction indicators of online food delivery employees: insights from employees' online reviews - Saydam, Mehmet Bahri; Altun, Ozlem; Karatepe, Tuna; Olorunsola, Victor; Naderiadib Alpler, Nazanin (Emerald Group Publishing Ltd, 2024)
Purpose-The present study sought to determine the main themes employees discussed in online reviews associated with satisfaction (pros) and dissatisfaction (cons). Design/methodology/approach-This study used qualitative content analysis to examine employee reviews working in India's largest food delivery company. Findings-The analyses revealed the existence of seven themes: company environment, employees, salary, work-life balance, company culture and values, flexibility and favoritism. Negative themes were associated with the work-life balance and favoritism themes. The results provided valuable insights into online food delivery platform employees' overall experiences based on social media information and aided in identifying key themes associated with various satisfaction levels. Originality/value-This study contributes to the literature by uniquely utilizing user-generated content from an employment search engine as a novel data source to investigate the factors influencing satisfaction and dissatisfaction among online food delivery employees. This approach represents a significant departure from traditional survey-based methods, filling a gap in the literature by offering insights directly from employees' unfiltered perspectives. By leveraging this innovative methodology, our research provides a fresh and nuanced understanding of the experiences and concerns of online food delivery workers, thereby adding substantial value to the fields of organizational behavior and human resource management.
Keywords: Content analysis; Gig economy; Foodservice industry; Job satisfaction; Leximancer; Online reviews